2021
DOI: 10.5603/gp.a2020.0164
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of the prognostic value of the neutrophil/ lymphocyte ratio and the platelet/lymphocyte ratio among advanced endometrial cancer patients

Abstract: Objectives: About 20% of endometrial cancer (EC) patients have advanced disease (FIGO III & IV) at the moment of diagnosis. An attempt to evaluate the prognostic value of biochemical markers of inflammation and classic endometrial cancer prognostic factors in the group of advanced EC (aEC) patients has been made in this study. Material and methods: Records of 266 patients treated in the Maria Sklodowska-Curie Memorial Cancer Centre and Institute of Oncology, Cracow Branch between the year 2006 and 2018 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Therefore, cancer is also associated with increased PLR values. A study from Poland reported that PLR was correlated with survival in patients with endometrium cancer [15]. High PLR levels were correlated with worse overall survival in oral squamous cell carcinoma patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cancer is also associated with increased PLR values. A study from Poland reported that PLR was correlated with survival in patients with endometrium cancer [15]. High PLR levels were correlated with worse overall survival in oral squamous cell carcinoma patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets and cancer cells interact in a pathological feed-forward loop in which the cancer cells activate platelets and platelets support cancer cells. Platelet counts are significantly elevated in endometrial cancer patients, and, in combination with other factors, are prognostic for presence of positive lymph nodes and worse prognosis [ 50 , 51 , 52 ]. Blood-based assays including platelet counts have also been shown to differentiate between endometrial cancer from atypical endometrial hyperplasia [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the effective compensation mechanism, normal platelet counts may mask highly hypercoagulative and proinflammatory cancer activity [17]. High platelet levels can lead to poor prognoses in various cancers, including pancreatic cancer, gastric cancer, colorectal cancer, endometrial cancer and ovarian cancer [18][19][20][21][22]. By responding to molecules that tumors produce to stimulate angiogenesis, platelets can cause thrombosis events that facilitate cancer progression [23].…”
Section: Discussionmentioning
confidence: 99%